OSMR induces M2 polarization of glioblastoma associated macrophages through JAK/STAT3 signaling pathway - Changcheng Xiao; Liming Tan; Liming Tan; Xiaofei Liu; Min Zhou; Ping Chen; Zhao Wang; Bing Wang (Frontiers in Oncology)
IntroductionVerify whether Onconstatin M receptor (OSMR) plays a regulatory role in the growth of glioblastoma (GBM) and explore its specific regulatory mechanism.MethodsIn vitro investigations were carried out using OSMR knockdown and treatment with JAK agonist Butyzamide (JAKa). Evaluate cell proliferation rate through CCK-8; Colony formation experiment to detect cell proliferation; Transwell experiment evaluates cell invasion; Cell scratch assay to detect cell migration; WB detects the expression levels of pathway related proteins JAK, p-JAK, STAT3, p-STAT3, and CCL-2; Flow cytometry analysis of apoptosis rate, cell cycle arrest rate, and proportion of M2 macrophages; RT-qPCR was implemented to identify the expression of M2 polarization factors CD206, CD163 and IL-10 in macrophages. In the in vivo experiment, SF188 cells were subcutaneously injected into mice’s right sides and divided into two groups: those with knocked down OSMR or those without. The knocked down OSMR group was divided into subgroups treated with DMSO containing or not containing JAKa. Subsequently, the tumor volume and weight of the mice were measured. RT-qPCR was utilized to assess the level of M2 polarization-related components in tumor tissues, while flow cytometry was employed to determine the M2 polarization ratio of macrophages in tumor tissues.ResultsKnocking down OSMR dramatically reduces tumor cell proliferation, invasion, and migration, accelerates cell death and cell cycle arrest, and lowers JAK and STAT3 phosphorylation as well as CCL-2 expression levels, all while decreasing the fraction of M2 macrophages. Furthermore, knocking down OSMR drastically lowered tumor development and M2 polarization levels of monocytes in tumor tissue. JAKa reversed the inhibitory effect of OSMR knockdown on GBM malignant development and macrophage M2 polarization in both in vitro and in vivo studies.ConclusionOSMR promotes the JAK/STAT3 signaling pathway, which promotes malignant glioblastoma growth and macrophages M2 polarization.